Three types of skarn in the northern part of the Moldanubian zone, Bohemian Massif - Implications for their origin - Drahota,P.; Pertold,Z.; Pudilova,M. (Journal of the Czech Geological Society, 2005)
The Holsice regionally metamorphosed Cpx-Grt skarn occurs in the north of the Moldanubian zone, Bohemian Massif. Several new skarn bodies were found by detailed mapping in the vicinity, and three different kinds of skarns were distinguished. The Holsice skarn consists of Cpx-Grt, and calc-silicate gneiss bands (cm). The garnet zoning reflects the post-peak metamorphic decompression after HP/HT regional metamorphism probably at approx. 800 °C and 12 kbars. The Zliv skarn is massive, and contains magnetite (high anomalies in magnetometry) without calc-silicate gneiss. Its Grt-Cpx, Cpx, Grt-Amp and Amp skarn types are poor in Al (hedenbergite, andradite, ferro-actinolite, cummingtonite). Grossular-almandine rich garnet from the Grt-Amp skarn equilibrated at 670 °C, 6-8 kbars (Grt-Amp geothermometry). The third type of skarn (Vapenka) occurs as a narrow contact zone (only 4-8 cm wide) between marble and orthogneiss and contains sulphides, scheelite and spessartine-rich garnet. The analysed minerals from the narrow skarn zone yielded high δ18O values, which are compatible with the isotopic composition of the orthogneiss. On the other hand, the δ18O values found in the Holsice and Zliv skarn bodies are not compatible with the hypothesis of originally contact metasomatic origin associated with metagranitoid rocks in the studied area, which have an isotopic composition of 6-10 ‰ δ18O. This fact also suggests that the hypothesis of skarn precursors as an integral part of the (volcano-) sedimentary series remains valid for these Moldanubian localities.
Keywords: Skarn; metamorphism; oxygen and carbon isotopes; Moldanubicum; Bohemian Massif